2020
DOI: 10.1002/hep4.1606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cirrhosis and Diagnosis Scenario in Metabolic‐Associated Fatty Liver Disease‐Related Hepatocellular Carcinoma

Abstract: Metabolic-associated fatty liver disease (MAFLD) is a major cause of liver-related complications, including hepatocellular carcinoma (HCC). While MAFLD-related HCC is known to occur in the absence of cirrhosis, our understanding of MAFLD-related HCC in this setting is limited. Here, we characterize MAFLD-related HCC and the impact of cirrhosis and screening on survival. This was a multicenter, retrospective, cohort study of MAFLD-related HCC. MAFLD was defined based on the presence of race-adjusted overweight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…This highlights the importance of increasing compliance to primary HCC surveillance among patients at risk for HCC, to increase the likelihood of such patients being diagnosed before the development of MVI. Unfortunately, compliance to HCC surveillance has been reported to be very poor in the real world, with most HCC patients diagnosed at a late stage (31)(32)(33)(34)(35). A recent nationwide USA study of 82,427 patients with cirrhosis reported that HCC surveillance took place in barely 10% of patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of increasing compliance to primary HCC surveillance among patients at risk for HCC, to increase the likelihood of such patients being diagnosed before the development of MVI. Unfortunately, compliance to HCC surveillance has been reported to be very poor in the real world, with most HCC patients diagnosed at a late stage (31)(32)(33)(34)(35). A recent nationwide USA study of 82,427 patients with cirrhosis reported that HCC surveillance took place in barely 10% of patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…112 Unfortunately, due to the low incidence of noncirrhotic NAFLD-related HCC, the current practice guidelines do not recommend routine HCC surveillance for noncirrhotic NAFLD. [113][114][115] Future prospective studies exploring the role of screening in noncirrhotic NAFLD-related HCC are required. Additionally, we need to confirm the applicability of screening protocols in practice guidelines for cirrhotic NAFLD-related HCC to enable early detection and improve the prognosis of this serious complication.…”
Section: Strategies To Decrease the Prevalence Of Nafld And Its Compl...mentioning
confidence: 99%
“…MAFLD encompasses a spectrum of liver conditions ranging from simple steatosis to steatohepatitis, fibrosis, and cirrhosis ( 5 ). The pathogenic process of MAFLD is well−thought−out as a systemic metabolic dysfunction state ( 6 ) and commonly linked to various metabolic disorders, including fibrosis and cirrhosis ( 7 ), liver cancer ( 8 ), obesity ( 9 ), type 2 diabetes (T2DM) ( 10 , 11 ), and even cardiovascular disease ( 12 ). It is worth noting that the clinical management and consequence of MAFLD patients are influenced strongly by the more aggressive phenotypes.…”
Section: Introductionmentioning
confidence: 99%